Students' Proficiency in Volleyball and Physical Fitness Level - Samsudin Samsudin (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aimed to conduct a comprehensive assessment of the physical fitness levels and fundamental abilities essential for playing volleyball, with a specific focus on eighth-grade students enrolled at SMP Negeri 3 Belo. The assessment aimed to provide valuable insights into the student's overall health and fitness levels and identify areas that require improvement to enhance their potential for excelling in volleyball. Material and Method. The research study comprised 27 students in class VIII enrolled in SMP Negeri 3 Belo to analyze the data collected from the participants using the SPSS Version 16.00 program. The research methodology adopted for this study is quantitative, and the data was collected through surveys, assessments, and other relevant methods. The study's primary objective was to identify the correlations and patterns in the data, and the results were analyzed using statistical tools and techniques to draw meaningful conclusions. Result. The fitness assessment has yielded promising results, with an average score of 18.14 indicating good physical fitness among the participants. Additionally, the basic volleyball skills test revealed that 14.3% of the participants displayed excellent skills, while 7.1% showed good skills. A majority of 42.7% fell under the medium skills category, followed by 21.4% of the participants with poor skills. The remaining 10.7% demonstrated very little skill in the sport. Conclusion. Based on the assessment of basic volleyball playing skills among class VIII students of SMP Negeri 3 Belo, it can be concluded that their performance falls under the moderate category, with an average score of 147.96. This indicates that while the students possess a basic understanding of volleyball techniques and rules, there is still room for improvement in terms of their overall proficiency